2013
DOI: 10.1136/bmjopen-2012-002154
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the effect of red blood cell transfusion on mortality: evidence from large-scale observational studies published between 2006 and 2010

Abstract: ObjectiveTo carry out a systematic review of recently published large-scale observational studies assessing the effects of red blood cell transfusion (RBCT) on mortality, with particular emphasis on the statistical methods used to adjust for confounding. Given the limited number of randomised trials of the efficacy of RBCT, clinicians often use evidence from observational studies. However, confounding factors, for example, individuals receiving blood generally being sicker than those who do not, make their int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 53 publications
0
41
1
4
Order By: Relevance
“…10,13 The results from our review indicate that receiving blood transfusion is protective against unplanned readmission. 21 A potential explanation for this finding may be that although blood transfusion is often associated with higher rates of postoperative complications, morbidity, and mortality, 1,18,21,29 it may be an effective way of dealing with those complications before leaving the hospital. That is, a patient who undergoes a large vascular spinal fusion procedure may be appropriately treated with blood transfusion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10,13 The results from our review indicate that receiving blood transfusion is protective against unplanned readmission. 21 A potential explanation for this finding may be that although blood transfusion is often associated with higher rates of postoperative complications, morbidity, and mortality, 1,18,21,29 it may be an effective way of dealing with those complications before leaving the hospital. That is, a patient who undergoes a large vascular spinal fusion procedure may be appropriately treated with blood transfusion.…”
mentioning
confidence: 99%
“…8,21,24 We found that postoperative complications were predictive in multiple studies, and others found that they were a common risk factor for 30-day readmission across multiple specialties. 8,18,21,24,25,27,30,32 Lovecchio et al 24 found that demographic factors, comorbid disease, and operative characteristics could not alone predict readmission rate, when complications remained as a covariate. Preoperative patient characteristics like diabetes, as shown above, increase the likelihood of complication, and these complications increase the risk of readmission.…”
mentioning
confidence: 99%
“…Benefits and risks of red blood cell (RBC) concentrate transfusion have intensively and controversially been discussed in various publications [1,2,3,4]. The occurrence of well-known serious adverse reactions (transfusion-related infection, haemolysis, allergic reaction, transfusion-related acute lung injury (TRALI) etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Estos pacientes son difíciles de catalogar porque a menudo tienen una mayor comorbilidad, y puede ser difícil definir si los peores resultados son debidos a las condiciones preexistentes y las comorbilidades de los pacientes, o a la transfusión por sí misma, ofreciendo una condición de sesgo para los pacientes que son transfundidos 4 . Además, se añade el hecho de que en diferentes estudios, las transfusiones mejoran poco la condición clínica del paciente, lo que actualmente cuestiona su efectividad clínica 5,6 .…”
Section: Situación Actualunclassified